2020
DOI: 10.1002/anie.202000489
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed Discrimination of Single Amino Acid Residues in Polypeptides in a Single SERS Hot Spot

Abstract: The SERS‐based detection of protein sequences with single‐residue sensitivity suffers from signal dominance of aromatic amino acid residues and backbones, impeding detection of non‐aromatic amino acid residues. Herein, we trap a gold nanoparticle in a plasmonic nanohole to generate a single SERS hot spot for single‐molecule detection of 2 similar polypeptides (vasopressin and oxytocin) and 10 distinct amino acids that constitute the 2 polypeptides. Significantly, both aromatic and non‐aromatic amino acids are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 45 publications
0
89
0
1
Order By: Relevance
“…27 They also used this approach to detect single amino acid residues in polypeptides. 61 Nanocavities realized by using DNA-based nanotechnology Over the last decade, the DNA origami technique has been consolidated into the state-of-the-art approach for the selfassembly of nanophotonic structures. 62,63 DNA origami is fabricated in a bottom-up manner by folding a "long" singlestranded DNA (ss-DNA) sequence (termed "scaffold", $8000 bases long) into a predesigned shape with the help of approximately 200 "short" ss-DNA sequences (termed "staples", $40 bases long and complementary to the scaffold sequencesee Fig.…”
Section: From Nano To Picocavities For High-resolution Single-moleculmentioning
confidence: 99%
“…27 They also used this approach to detect single amino acid residues in polypeptides. 61 Nanocavities realized by using DNA-based nanotechnology Over the last decade, the DNA origami technique has been consolidated into the state-of-the-art approach for the selfassembly of nanophotonic structures. 62,63 DNA origami is fabricated in a bottom-up manner by folding a "long" singlestranded DNA (ss-DNA) sequence (termed "scaffold", $8000 bases long) into a predesigned shape with the help of approximately 200 "short" ss-DNA sequences (termed "staples", $40 bases long and complementary to the scaffold sequencesee Fig.…”
Section: From Nano To Picocavities For High-resolution Single-moleculmentioning
confidence: 99%
“…As shown in Fig. 2, the N-terminal of each monomer was prolonged with a 16aa-long sequence inspired to the well-known three-dimensional Leucine zipper structural motif [21]. Details about how the elongation has been designed can be found in Section S2 in the Electronic Supplementary Material (ESM).…”
Section: Methodsmentioning
confidence: 99%
“…This enabled the detection of twelve different EV membrane proteins using antibodies. Signals were further amplified by attaching anti-CD63-modified gold nanostars to captured EVs and utilizing the plasmonic coupling of these to the underlying gold surface [114][115][116]. The authors showed the clinical potential of this approach using ascitic fluid from 20 patients with ovarian cancer and 20 controls.…”
Section: Spr Arraysmentioning
confidence: 99%